Mobilising private climate finance for sustainable energy access and climate change mitigation in Sub-Saharan Africa. (2nd January 2021) - Michaelowa, Axel; Hoch, Stephan; Weber, Anne-Kathrin; Kassaye, Ruth; Hailu, Tesfaye
ABSTRACT: Ensuring access to sustainable energy is equally relevant for both sustainable development and climate change mitigation. Mobilising private finance in Sub-Saharan African (SSA) countries will, in turn, be of crucial importance for achieving both Sustainable Development Goal (SDG) 7 – which calls for universal energy access – and climate change mitigation goals defined under the Paris Agreement. In this paper, we assess how UNFCCC-backed climate finance instruments have engaged private investment for energy-focused climate mitigation in SSA. Based on this assessment, we develop recommendations for public climate finance institutions. Our work builds on documentary and database analysis and interviews, as well as participatory methodologies applied at a stakeholder workshop conducted in Kampala, Uganda, in 2018. Three case studies from Ethiopia, Madagascar and South Africa illustrate how climate finance interacts with domestic policy instruments, including in relation to the Kyoto Protocol's Clean Development Mechanism, South Africa's domestic renewable energy auctions, and the Green Climate Fund. The paper finds that there is no 'catch all' success model and approaches need to be tailored to local circumstances. Key policy insights International market mechanisms and climate finance can be key catalysts for private multibillion-dollar investment in energy access and climate mitigation, even under the challenging conditions facing many SSA nations. Market mechanisms need to be managed well to provide the private sector with the certainty needed to commit to fresh investments. A programmatic approach with standardised baseline and monitoring methodologies should be anchored in the next generation of project-based market mechanisms under Paris Agreement Article 6. Linking international and regional development programmes with the international carbon market might be an option for closing financing gaps, while at the same time increasing synergies between climate goals and SDGs.